OC16: Electro-clinical features in epileptic children with chromosome 15qduplication syndrome. (March 2022) - Dangles, M.T.; Malan, V.; Dumas, G.; Nabbout, R.; Kaminska, A.; Eisermann, M.
Abstract : We aimed to describe epilepsy and EEG patterns related to vigilance states and age, in chromosome15-long-arm-duplication-syndrome (dup15q) children with epilepsy, in both duplication types: interstitial (intdup15) and isodicentric (idic15). Methods: Clinical data and 70 EEGs of 12 patients (5 intdup15, 7 idic15), followed from 4.5m.oto 17y4m (median follow-up 8y3m), were retrospectively reviewed. EEGs were analyzed visually and using power spectrum analysis. Results: Seventy video-EEGs were analyzed (1-16 per patient, median 6), follow-up lasting up to 8y10m (median 4y2m): 25 EEGs in intdup15(8m.o to 12y.o, median 4y6m) and 45 EEGs in idic15 (7m.o to 12 y.o, median 15m).Epilepsy: 6 Westsyndrome (WS) (2intdup15, 4idic15);4 Lennox-Gastaut syndromes (LGS) (1 intdup15, 3 idic15), 2 evolving from WS; focal epilepsy (3 intdup15). In idic15, WS displayed additional myoclonic seizures (3), atypical (4) or no hypsarrhythmia (2) and posterior predominant spike and polyspike bursts (4). Beta-bandrapid-rhythms (RR):present in 11 patients, power decreased during non-REM-sleep, localization shifted from diffuse to anterior, peak frequency increased with age. Conclusion: WS with peculiar electro-clinical features and LGS, along with beta-band RR decreasing in non-REM-sleep and shifting from diffuse to anterior localization with age are recognizable features pointing towards dup15q diagnosis in children with autism spectrum disorder and developmental delay. This study describes electroclinical features in both interstitial and isodicentric duplications of chromosome 15q, in epileptic children, including some recent extensions regarding sleep features; and illustrates how the temporo-spatial organization of beta oscillations can be of significant help in directing towards dup15q diagnosis hypothesis.